Phylogenetic analyses and species delimitation of Aconurella Ribaut (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) in China based on molecular data - Yan, Minhui; Bao, Jiangwei; Luo, Miaoqing; Gao, Yao; Dietrich, Christopher H.; Duan, Yani (Zootaxa, 2022)
The grassland leafhopper genus Aconurella is widespread in the Old World. Species of this genus are difficult to identify by traditional morphological characters but the morphology-based species classification in this genus has not previously been tested using molecular data. This study analysed DNA sequence data from two mitochondrial genes (COI, 16S) and one nuclear gene (ITS2) to infer the phylogenetic relationships and status of five previously recognized Aconurella species and compare the performance of different molecular species-delimitation methods using single and multiple loci. The analysis divided the included haplotypes into five well-supported subclades, most corresponding to existing morphology-based species concepts. However, different molecular species delimitation methods (jMOTU, ABGD, bPTP, GMYC and BPP) yielded somewhat different results, suggesting the presence of between 4 and 8 species, sometimes lumping the haplotypes of Aconurella diplachnis and Aconurella sibirica into a single species or recognizing multiple putative species within Aconurella prolixa. Considering the different results yielded by various methods employing single loci, the BPP method, which combines data from multiple loci, may be more reliable for delimiting species of Aconurella. Our results suggest that the morphological characters previously used to identify these species are reliable and adequately reflect boundaries between genetically distinct taxa.